2007
DOI: 10.1590/s0034-72992007000400011
|View full text |Cite
|
Sign up to set email alerts
|

Proposta de instrumento comportamental para avaliar a atenção auditiva sustentada

Abstract: A atenção sustentada e vigilância são alguns dos processos que caracterizam a atenção e fundamentais para o desenvolvimento de algumas habilidades. OBJETIVO: Propor um instrumento comportamental simples, de fácil e rápida aplicação para auxiliar na avaliação da habilidade de atenção auditiva sustentada. Estudo prospectivo. MATERIAL E MÉTODO: Crianças voluntárias de 6 a 11 anos de idade, 139 do gênero feminino e 141 do masculino. O teste foi denominado Teste da Habilidade da Atenção Auditiva Sustentada e basead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
0
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 31 publications
9
25
0
14
Order By: Relevance
“…There were no statistically significant differences between genders in this study (Table 3); this finding concurs with those of Keith 23 and Feniman 5 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There were no statistically significant differences between genders in this study (Table 3); this finding concurs with those of Keith 23 and Feniman 5 .…”
Section: Discussionsupporting
confidence: 92%
“…The mean decreased vigilance value was 4 in the cleft lip and palate group, which was lower compared to controls and to the mean value in Feniman's paper. 5 Asbjornsen et al 3 applied a dichotic consonantvowel test and found that the group with a history of otitis media performed worse in sustaining attention to auditory events, which was similar to our findings. Klausen et al 33 used a similar dichotic consonant-vowel test and concluded that OME affects the ability to persist and focus attention on auditory events.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…O THAAS, originalmente aplicado em forma de CD, em diferentes casuísticas (KEITH, 1994;FENIMAN et al, 2007;LEMOS;FENIMAN, 2010;MONDELLI et al, 2010;PICOLINI et al, 2010;FENIMAN et al, 2012;JOSÉ, 2013, BORBA, et al, 2016FERNANDES, 2017) …”
Section: Tecnologia Da Informação é O Conjunto De Recursos Não Humanosunclassified
“…A atenção auditiva sustentada é analisada considerando quanto o sujeito mantém a atenção por um período de tempo determinado (FENIMAN et al, 2007a).…”
Section: Atenção Auditiva Sustentada E Delunclassified